2019
DOI: 10.1021/acs.iecr.8b04623
|View full text |Cite
|
Sign up to set email alerts
|

Development of Iron Encapsulated Hollow Beta Zeolites for Ammonia Selective Catalytic Reduction

Abstract: We designed a high activity of NH3-SCR catalysts based on hollow beta zeolite nanospheres with encapsulated iron species, and these iron encapsulated hollow beta zeolites exhibited higher activity at low temperature (the NO x conversion ∼45% versus > ∼82% at 200 °C) due to the synergy between the Fe3+ species and Brønsted acid sites. In addition, the iron encapsulated hollow beta zeolites possessed an extensive operating-temperature window (225–500 °C, the NO x conversion was > ∼92%) owing to the hollow stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Many zeolites with various framework types, such as MFI, BEA, CHA, AEI, ERI, KFI, AFX, DDR, RTH, SFW, LEV, LTA, RHO, and UFI, have been investigated as SCR catalysts [3][4][5][6][7][8]. Iwamoto et al [9,10] first reported the catalytic activity of Cu-ZSM-5 for the decomposition of NO.…”
Section: Introductionmentioning
confidence: 99%
“…Many zeolites with various framework types, such as MFI, BEA, CHA, AEI, ERI, KFI, AFX, DDR, RTH, SFW, LEV, LTA, RHO, and UFI, have been investigated as SCR catalysts [3][4][5][6][7][8]. Iwamoto et al [9,10] first reported the catalytic activity of Cu-ZSM-5 for the decomposition of NO.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal@zeolite catalysts have drawn significant attention owing to their superior ability on enhancing catalytic stability and product selectivity and have been applied in many fields. Wang et al reported an extraordinary furan selectivity of 98.7% in furfural hydrogenation for Pd@S-1 with the core–shell structure synthesized by the solvent-free crystallization method, which was significantly higher than the conventional Pt/S-1 catalyst (5.6%). Liu et al designed a hollow Beta zeolite encapsulated Pt catalyst for NH 3 -SCR reaction, and the catalyst exhibited outstanding catalytic property at low temperatures, thermal durability, and SO 2 resistance. Wei et al observed the shape-selective catalytic performance of hollow S-1 zeolite encapsulated Pd nanoparticles for the hydrogenation of 3-methyl-2-butenal and cinnamaldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existence of the sole microporous channel in a conventional MEL zeolite is not conducive to the reaction involving bulk molecules. Especially in liquid-phase alkylation, the hierarchically structured zeolites with additional mesopores in addition to the inherent micropores of zeolites exhibited more outstanding properties than pure micropores. , In general, hierarchical zeolites can reduce steric hindrance and improve the transportability of guest molecules through the interconnected microporous–mesoporous networks, and many strategies have been developed to prepare the hierarchically structured zeolites in the following years, such as hard-template method, , soft-templating method, , post-synthetic demetallation method, , and so forth. In the present research, the novel hierarchical MEL zeolites were fabricated by the desilication and recrystallization of silicalite-2 under tetrabutylammonium hydroxide (TBAOH) solution.…”
Section: Introductionmentioning
confidence: 99%